(untitled) (Eurasian Journal of Philology Science and Education, 2021)
The article is devoted to the problem of the broad understanding of the communicative-grammatical term “distribution”. The purpose of the article – to clarify the concept of distribution, to establish the par The research material: the data of Internet and radio discourses. Cognitive, distributive, contextual, consultative, cultural, sociolinguistic analyzes, the research methods: the method of discourse analysis and the method of semantic differential. The study was carried out in line with the sociolinguistic approach, it identifies various types of distributions that actively influence the formation of a positive or negative ecology of the communicative act and correspond to the rhythm of life of the modern Russian language. New types of distributive constructs are identified and described, illustrated with examples from modern media discourse. Particular attention is paid to the analysis of socio-communicative and psychoemotional situations as one of the distribution constructs. The modern mass media informational and creative functions are demonstrated, the implementation of which ensures the creation of word forms to denote new concepts. Comparison of lexical, grammatical and innovative-creative distributions marked by global expressivization and emotionalization is carried out. The scientific study proposes a non-trivial approach to the traditional linguistic concept of distribution. The practical significance: the opportunity to use the materials and conclusions for further sociocultural and linguistic research of modern mass media, the future prospects: discount, distant, deferred, distant, action, situation, event, confession, culture, social environment, chapter context / sections / parts of the book, micro / macro context, vertical context of the entire book, megacontext, global context. The result of the study is the identification and characterization of new distribution constructs: situational (in its various varieties), actional, reactive (stimulus ‘vs’ reaction), essential.